2020
DOI: 10.1007/s00436-020-06878-y
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii seroprevalence in beef cattle raised in Italy: a multicenter study

Abstract: Toxoplasmosis represents an important public health issue, with the consumption of raw or undercooked meat being a major way of human infection. The role of beef in the transmission of the parasite to humans is questioned due to lower quantity of tissue cysts compared with other meat-producing species. However, the habit of consuming raw beef is regionally diffused, and the risk posed by Toxoplasma gondii infection in cattle should not be overlooked. Therefore, to update information on T. gondii in cattle rear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
3
9
0
Order By: Relevance
“…Toxoplasmosis is widespread and its seroprevalence in livestock vary widely, reaching high values in sheep (98.9%), goats (95.2%), cattle (93.5%) and pigs (96.6%) reviewed in [1,[23][24][25]. The seroprevalence rates, at individual and farm level, in livestock reported here are in line with the results from different studies conducted in other Italian regions [13,15,16,26]. According to these studies, a higher seroprevalence was recorded in small ruminants (sheep and goats) than in cattle and water buffaloes due probably to differences in susceptibility to T. gondii infection and to differences in farm management.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Toxoplasmosis is widespread and its seroprevalence in livestock vary widely, reaching high values in sheep (98.9%), goats (95.2%), cattle (93.5%) and pigs (96.6%) reviewed in [1,[23][24][25]. The seroprevalence rates, at individual and farm level, in livestock reported here are in line with the results from different studies conducted in other Italian regions [13,15,16,26]. According to these studies, a higher seroprevalence was recorded in small ruminants (sheep and goats) than in cattle and water buffaloes due probably to differences in susceptibility to T. gondii infection and to differences in farm management.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have been conducted to establish the seroprevalence of T. gondii in livestock across the Italian regions. In central-northern Italy, seroprevalence ranged from 27.5% to 60.6% at individual animal level [13,14] and up to 97.0% [13] at farm level in small ruminants whereas a prevalence value of 68.4% was reported in cattle farms [15]. The same epidemiological scenario was encountered in southern and insular regions, where high prevalence values, up to 87.0%, were reported in small ruminant farms [16].…”
Section: Introductionmentioning
confidence: 66%
“…Results herein reported show the widespread presence of T. gondii in sheep farms in Sardinia, as recently reported in pigs and cattle on the same island (Pipia et al 2018;Gazzonis et al 2020). The seroprevalence of T. gondii recorded in the present survey (36.2%) is considerably lower than that reported in Sardinia more than 10 years ago (51.3%) (Natale et al 2007).…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, the presence of T. gondii in the study area was previously extensively reported with the detection of specific antibodies or parasitic DNA in different domestic [30][31][32] and wild host species [20,27], demonstrating the presence of both a domestic and a sylvatic cycle in this area. The animals admitted to the WCR are usually individuals living near urban centers; for this reason, they are more frequently subject to anthropogenic trauma (e.g., impact with windows and cars), and more easily identifiable and referable to WRCs.…”
Section: Discussionsupporting
confidence: 57%